Morphological and molecular characterization of the trematodes (Digenea: Acanthocolpidae and Cryptogonimidae) of the black-spotted croaker (Protonibea diacanthus) (Teleostei: Sciaenidae) in northern Australia - Megan Porter; Diane P. Barton; Xiaocheng Zhu; Shokoofeh Shamsi (Parasitology)
Abstract